A NEW DIGITAL MARKETING AREA FOR E-COMMERCE BUSINESS - Reza Nur Rosiyana; Melyana Agustin; Ivan Kalka Iskandar; Senny Luckyardi (International Journal of Research and Applied Technology (INJURATECH), 2021)
Digital marketing is a familiar thing in the business world. One of them is a Tiktok Shop. Tiktok Shop is a new feature in Tiktok application, officially launched in April 2020. Tiktok shop has become very popular among e-commerce businesses and customers who often shop online, because this application provides an attractive and easy interface for product marketing and purchasing products. The background of this research is because tiktok shop get viral so fast as a new e-commerce media and can even run in parallel other e-commerce. Therefore, this research purposes for knowing why this e-commerce can quickly viral and be used by many people. Furthermore, it can compete with other e-commerce and become the choice of business people and customers in conducting business processes. This research method is based on observations and interviews with various parties, two as business people and customers. The results of this study are in the form of exposure based on the research objectives presented, which enables us to have concrete evidence that this tiktok shop has influence and is worthy of being used as a new e-commerce along with other e-commerce in conducting business processes. Discuss research to get answers about the influence of Tiktok Shop on marketing. which resulted in the conclusion that Tiktok Shop could be a new alternative tool for business people in carrying out their business processes. The benefit of this research is to see how far the development of tiktok shops among the public and business people.